Oxygen Doping Effects on the Re-entrant Point of Vortex Melting Line in Bi2Sr2CaCu2O8+δ and YBa2Cu3O7-δ Superconducting System - D. Ulfaty; M. Diantoro; W. Loeksmanto; M.O. Tjia (Institut Teknologi Bandung, 2003)
The complexity of vortex morphology of high Tc superconductor is marked among others by the existence of “re-entrant” phenomena of vortex melting lines in the B-T diagram. This peculiar behavior has its origin in the large anisotropy, disorder and thermal fluctuation effects. Materials having those characterictics are Bi2Sr2CaCu2O8+δ (BSCCO-2212) and YBa2Cu3O7-δ (YBCO-123). The re-entrant point (B*,T*) can be regarded as the intersection point between the low field melting curve and the high field melting curve. The values of B* and T* generally depend on the critical temperature (Tc), anisotropy factor (ε) and penetration depth (λ). The results of analysis based on the data of Tc, ε, and λ from the samples of BSCCO-2212 and YBCO-123 single crystals show that B*>Bc1 and T*<Tc with Tc-T* ranging from 0.13K to 0.28K for BSCCO-2212 and 0.05 to 0.06 for Y-123 samples, while the value of B* spans the range of 0.35G – 0.7G and 0.40G – 0.45G for BSCCO-2212 and YBCO-123 respectively. It is emphasized however, that the results obtained are strongly depend on the choices of Lindemann constant cL and Ginzburg parameter G.